Attitudes to personalised versus standardised practice in traditional Chinese medicine: a national cross-sectional survey of practitioners in China. (October 2016) - Liu, Mengyu; Zhang, Chi; Zha, Qinglin; Yang, Wei; Yuwen, Ya; Zhong, Linda; Bian, Zhaoxiang; Han, Xuejie; Lu, Aiping
Abstract: Background: Critics argue that traditional Chinese medicine should focus on a personalised patient experience, and that standardised practices risk killing the traditional art. The development of clinical practice guidelines (CPGs) for Chinese medicine, which began 30 years ago, has risen remarkably over the years. However, for individual practitioners for whom these guidelines are recommended, the impact of the CPGs on clinical practice and their acceptability remain unknown. The aim of this study was to investigate acceptability of standardisation guidelines in traditional Chinese medicine practitioners in China, and the effect of CPGs on clinical practice. Methods: We did a cross-sectional questionnaire survey of 4503 Chinese medicine practitioners aged 20–65 years from 28 provinces in mainland China, chosen from a random sample of hospitals in a defined geographical area. The surveys were administered between July, 2012, and January, 2013. Self-administered questionnaires were used to collect information about acceptability, application, practice change, and outcomes of implementation of CPGs. Basic classification data on specialties and year of qualification were also collected. The institutional ethics committee approved the study protocol. Written informed consent was obtained from all participants. Findings: We obtained data for 4495 practitioners, of whom 4461 had complete responses to all items. 3847 (86%) of 4495 Chinese medicine practitioners reported that they were familiar with CPG recommendations, and overall 2265 (50%) adhered to the guidelines. 48 (33%) of 145 doctors with more than 30 years' experience and 712 (52%) of 1369 doctors with less than 5 years' experience reported that they never used CPGs. Doctors in nine specialties showed a modest degree of homogeneity in how effective they regarded Chinese medicine with respect to diagnosis and treatment, and were generally positive (ranging from 29 [73%] of 40 ophthalmology specialists to 255 [97%] of 263 anorectal specialists). Most doctors regarded CPG-recommended therapies as safe (4142 [92%] of 4491), economic (3739 [84%] of 4462), and effective (3402 [76%] of 4452). After a comprehensive assessment of CPGs, 2714 (61%) of 4461 practitioners regarded the guidelines as acceptable and 839 (19%) 4461 said they would accept them after revision. Interpretation: To our knowledge, our study provides the first evidence that most Chinese medicine practitioners support CPG use, on the basis of data from a large-scale survey. Chinese medicine practitioners were willing to embrace and implement both standardised and personalised care to revolutionise their clinical practice. The results also underscore the variation among practitioners in the use of CPGs according to professional activities and specialty. This survey suggests that health policy makers can achieve standardised practice and personalisation combined with CPG application. Funding: Chinese Ministry of Finance (number ZYYBZ-2012).